Michiel de Swaen's digtkonde, A. Dacier en P. Corneille : een bronnenonderzoek - Vanderheyden, Jan F. (Gent : Erasmus, 1954)
Bibliotheek Camille Huysmans
Dedicator: Vanderheyden, Jan F., dedicatee: Huysmans, Camille
Nederlands
Brochure
Keywords: letterkunde